2019
DOI: 10.1038/s41386-019-0515-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic seizure therapy (MST) for major depressive disorder

Abstract: Electroconvulsive therapy (ECT) is effective for major depressive disorder (MDD) but its effects on memory limit its widespread use. Magnetic seizure therapy (MST) is a potential alternative to ECT that may not adversely affect memory. In the current trial, consecutive patients with MDD consented to receive MST applied over the prefrontal cortex according to an open-label protocol. Depressive symptoms and cognition were assessed prior to, during and at the end of treatment. Patients were treated two to three t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 62 publications
(79 citation statements)
references
References 28 publications
3
74
1
1
Order By: Relevance
“…Thus, we explored the association of MST with suicidality in a secondary analysis of a recently published open-label study on MST for TRD. 22 We hypothesized that MST would be associated with clinically meaningful rates of remission from suicidality as measured by the Beck Scale for Suicidal Ideation (SSI). We also explored whether the association of MST with suicidality differed among different MST stimulation frequencies in a sensitivity analysis.…”
Section: Thismentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, we explored the association of MST with suicidality in a secondary analysis of a recently published open-label study on MST for TRD. 22 We hypothesized that MST would be associated with clinically meaningful rates of remission from suicidality as measured by the Beck Scale for Suicidal Ideation (SSI). We also explored whether the association of MST with suicidality differed among different MST stimulation frequencies in a sensitivity analysis.…”
Section: Thismentioning
confidence: 99%
“…In the original study, 22 baseline suicidality, as defined by a score greater than 0 at the initial study visit on the Beck SSI, a validated 19-item scale used to quantify suicidality with a range from 0 to 38. 26 The main analyses in the present report focus on the 67 participants with baseline suicidality who were defined as adequate trial completers in that they completed at least 8 MST sessions.…”
Section: Overall Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The activation of the Hipp during ECT is hypothesized to be associated with the treatment related cognitive side effects 30,35,36 . MST treatments appear to have only minimal if any cognitive side effects 34 . The lack of cognitive side effects after MST is believed to be related to the focality of the induced effective field during stimulation 63 .…”
Section: Discussionmentioning
confidence: 99%
“…MST is a novel seizure inducing, neuromodulatory treatment for MDD with a similar efficacy as ECT [31][32][33] . By contrast, a large MST clinical trial that included an extensive cognitive battery found that MST had only minimal impact on autobiographical memory consistency 34 . The lack of cognitive side effects after MST is believed to be related to the focality of the induced effective field, and the sparing of hippocampal direct activation during treatment 30,35,36 .…”
Section: Introductionmentioning
confidence: 95%